2011
DOI: 10.1242/jcs.072181
|View full text |Cite
|
Sign up to set email alerts
|

Protein O-mannosyltransferases participate in ER protein quality control

Abstract: In eukaryotic cells, proteins enter the secretory pathway at the endoplasmic reticulum (ER) as linear polypeptides and fold after translocation across or insertion into the membrane. If correct folding fails, many proteins are O-mannosylated inside the ER by an O-mannosyltransferase, the Pmt1p-Pmt2p complex. The consequences of this modification are controversial and the cellular role of the Pmt1p-Pmt2p complex in this respect is unclear. Here, we have identified the binding partners of yeast Pmt1p and Pmt2p. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…O-Man glycosylation in yeast has multiple functions including those ascribed to O-GalNAc glycosylation in metazoans, i.e., roles for conformation, stability, and secretion of proteins (1). In yeast Pmt1p/Pmt2p, directed O-Man glycosylation has been demonstrated to play a role for ER protein quality control (43), and more recently the yeast Pmt1/2 mannosyltransferase complex was demonstrated to serve as a termination sensor of futile protein folding in ER (37).…”
Section: Resultsmentioning
confidence: 99%
“…O-Man glycosylation in yeast has multiple functions including those ascribed to O-GalNAc glycosylation in metazoans, i.e., roles for conformation, stability, and secretion of proteins (1). In yeast Pmt1p/Pmt2p, directed O-Man glycosylation has been demonstrated to play a role for ER protein quality control (43), and more recently the yeast Pmt1/2 mannosyltransferase complex was demonstrated to serve as a termination sensor of futile protein folding in ER (37).…”
Section: Resultsmentioning
confidence: 99%
“…O-linked mannosyl modification of secretory proteins in the ER is essential in yeast (Gentzsch and Tanner 1996) and required for cell wall integrity as well as normal morphogenesis (Strahl-Bolsinger et al 1999). The role of O-linked glycosylation in ER quality control processes remains unclear although investigators have reported influences of specific pmt mutations on turnover rates of misfolded glycoproteins (Harty et al 2001;Vashist et al 2001;Hirayama et al 2008;Goder and Melero 2011) and the PMT genes are upregulated by activation of the UPR (Travers et al 2000).…”
Section: Maturation Of Secretory Proteins In the Er: Protein Glycosylmentioning
confidence: 99%
“…Some of them are more protected against degradation [123,125], while others are degraded by the ERAD pathway [124,126]. Very recently, evidence was presented that Pmt1-Pmt2 complexes have the capacity to interact with ER chaperones involved in oxidative protein folding (Pdi1 and Ero1); the Hrd1 complex, which is functioning in ERAD; and the p24 protein complex, which participates in ER export of GPI-anchored proteins [127]. A model has been suggested where Pmt1-Pmt2 complexes directly assist protein folding of the GPI-anchored protein Gas1.…”
Section: Protein O-mannosylation and Er Homeostasismentioning
confidence: 99%